Incidencia de la contaminación atmosférica en el asma bronquial en niños menores de 10 años en la comunidad sol brisa del sector Bypas del Cantón Babahoyo los Ríos primer periódo 2018 - Molina Quiroz, Roxana Paola (2018)
Asthma is a chronic inflammatory disorder of the airways in which many cells and cell elements, such as eosinophils, mast cells, lymphocytes, macrophages, neutrophils and epithelial cells play a very important role in the inflammatory responses produced by different types of allergens. This research study, whose objective is to identify the age range that is most affected by childhood asthma, determine the incidence of constants such as socioeconomic status, sex, race to suffer from childhood asthma, prevent complications that develop in patients with asthma child, promote habits of prevention of predisposing factors. In the first chapter the objective, the problematic, and the justification of the study are made known. In the second chapter, the theoretical framework, we expose the definition, main risk factors and complications of asthma both locally and globally and shows the reader the most relevant aspects to take into account when carrying out a project of this nature. Chapters three and four report on the investigations that were carried out and the results of the same. The fifth chapter shows according to the survey work which are the main risk factors to avoid complications such as asthmatic crisis that can put the life of the patient at risk. Finally, at the closing are the conclusions and recommendations that should be taken into account on childhood asthma